PELAKSANAAN PENDAMPINGAN KEGIATAN TEKNOLOGI INFORMASI DI SD MUHAMMADIYAH PANDES SEBAGAI UPAYA UNTUK PENINGKATAN SUMBER DAYA MANUSIA DALAM MENGOPTIMALKAN TEKNOLOGI INFORMASI - Suraya .; Dina Andayati; Syukri Adbullah (JURNAL GAUNG INFORMATIKA, 2020)
Improving the quality of human resources in an organization becomes an obligation, especially in increasing teacher resources in the world of education. The use of information technology is now a necessity for teachers to help the learning process and in managing school administration. In the implementation of assistance to community service activities, assistance has been carried out in relation to optimizing information technology in supporting teachers in the learning process and in the administration ofteachers in managing records. The method of activities carried out is to identify the problems that exist in SD Muhammadiyah Pandes, especially those related to information technology and provide assistance to teachers and administration. The teachers are assisted in the development of making information technology-based teaching materials and administrative managers by making electronic records. The results of dedication carried out is providing training for teachers to be able to develop teaching materials based on information technology using the Sparkol application and quiz creator as well as for administration by using information technology-based archive applications with Arterial applications.